2018
DOI: 10.4103/jmh.jmh_121_17
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency anemia with menorrhagia: Ferric carboxymaltose a safer alternative to blood transfusion

Abstract: Background:Menstrual disorder accounts for 5%–10% of the women presenting with iron deficiency anemia (IDA) in the perimenopausal age group. Heavy menstrual bleeding in this age group leads to severe anemia and frequently requires blood transfusion which has its own adverse effects. We today have ferric carboxymaltose (FCM) as a safer alternative to blood transfusion.Objective:The objective of the study is to evaluate the safety and efficacy of FCM in treating anemia in patients of menorrhagia. Thus avoiding b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 10 publications
2
18
0
2
Order By: Relevance
“…Menstrual duration in this study was found to have a negative correlation with Hb levels (b = -0.249; 95% CI = -0.49 to -0.007; p <0.05). This finding is in line with the theory that regular menstruation can cause iron loss [23]. Our study supports a previous research study that adolescent girls with menstrual periods ≥5 days have 2.4 higher risk of developing anemia compared to those with the menstrual periods <5 days [15].…”
Section: Discussionsupporting
confidence: 93%
“…Menstrual duration in this study was found to have a negative correlation with Hb levels (b = -0.249; 95% CI = -0.49 to -0.007; p <0.05). This finding is in line with the theory that regular menstruation can cause iron loss [23]. Our study supports a previous research study that adolescent girls with menstrual periods ≥5 days have 2.4 higher risk of developing anemia compared to those with the menstrual periods <5 days [15].…”
Section: Discussionsupporting
confidence: 93%
“…The excessive blood loss during the menstrual period may contribute to iron deficiency anemia (IDA) to the subjects. 23 Our study results are corroborating with the reports by Weldekedan et al 24 It is a known fact there is a relationship between iron deficiency anemia and irregular cycles among the women, but we could not find any association between the irregularity in menstrual cycle with the prevalence of anemia in pregnant ladies of our study population. Study by Sreelekshmi et al also revealed similar results in a study conducted among tribal women at Palakkad district, Kerala.…”
Section: Discussionsupporting
confidence: 92%
“…In premenopausal women, heavy menstrual bleeding (HMB) is a frequently encountered cause for IDA and mild cases may be treated with a trial of oral iron depending on patient tolerability . Total iron absorption with daily oral supplementation is <10 mg/d such that moderate‐to‐severe anemia from HMB will require IV iron to keep up with the losses and achieve rapid and safe resolution of anemia . Men and women presenting with IDA in the absence of known pathology should be evaluated for other causes of blood loss and a gastroenterology referral should be considered.…”
Section: Diagnosis and Management Of Iron Deficiency Anemia In Adultsmentioning
confidence: 99%
“…13 Total iron absorption with daily oral supplementation is <10 mg/d such that moderate-to-severe anemia from HMB will require IV iron to keep up with the losses and achieve rapid and safe resolution of anemia. [14][15][16] Men and women presenting with IDA in the absence of known pathology should be evaluated for other causes of blood loss and a gastroenterology referral should be considered. If no cause can be identified, alternative inflammatory, absorptive, or genetic etiologies should be considered.…”
Section: Iag Nos Is and Manag Ement Of Iron Defi Cien C Y Anemia mentioning
confidence: 99%